Fast dissolving strips: A novel approach for the delivery of verapamil - S Kunte; P Tandale (Wolters Kluwer Medknow Publications, 2010)
Objective: Fast dissolving drug delivery system offers a solution for those patients having difficulty in swallowing tablets/capsules etc. Verapamil is a calcium channel blocker used as an antianginal, antiarrhythmic, and antihypertensive agent with extensive first pass metabolism which results in less bioavailability. This work investigated the possibility of developing verapamil fast dissolving strips allowing fast, reproducible drug dissolution in the oral cavity; thus bypassing first pass metabolism. Materials and methods: The fast dissolving strips were prepared by solvent casting technique with the help of HPMC E6 and maltodextrin. The strips were evaluated for drug content uniformity, film thickness, folding endurance, in vitro disintegration time, in vitro dissolution studies, surface pH study, and palatability study. Results: Official criteria for evaluation parameters were fulfilled by all formulations. Disintegration time showed by formulations was found to be in range of 20.4-28.6 sec. Based on the evaluation parameters, the formulation containing 2% HPMC E6 and 3.5% maltodextrin showed optimum performance against other formulations. Conclusion: It was concluded that the fast dissolving strips of verapamil can be made by solvent casting technique with enhanced dissolution rate, taste masking, and hence better patient compliance and effective therapy